An Exploratory Pharmacogenetic Pilot Study of Two Reverse Transcriptase Inhibitors, Tenofovir Alafenamide Fumarate and Tenofovir Disoproxil Fumarate - Derek E. Murrell; Benjamin C. Kennard; Maria E. Bertoni; David B. Cluck; Jonathan P. Moorman; Stacy D. Brown; Kesheng Wang; Michelle M. Duffourc; Sam Harirforoosh (Drugs in R&D)
Abstract Background and Objectives The nucleoside reverse transcriptase inhibitors tenofovir alafenamide fumarate and tenofovir disoproxil fumarate are frequently employed in treating human immunodeficiency virus. Further, each form of tenofovir requires laboratory monitoring to determine efficacy and tolerability among patients. This study sought to investigate the relationship, if any, of single nucleotide polymorphisms (SNPs) and selected clinical parameters. Methods The study population, predominantly Caucasian males with a median age of 53.0 years [interquartile range 46.0–59.0], was assayed for genetic variations using an iPLEX ADME PGx Pro v1.0 Panel. Results Although several SNP relationships were found with both forms of tenofovir, many of the reported SNPs were displayed only in the comprehensive regimen grouping, making it difficult to distinguish between the two prodrug forms. Conclusions Being an exploratory study, the findings of this substudy serve as potential avenues for further research.